Use of Prophylactic Aspirin in patients with previous history of Pre-eclampsia - Safoora Anjum, Salma Khalid, Arjumand Mahmood, Amina Saleem, Saima Rafique,Tahira Rizwan (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Aspirin is considered a safe and secure prophylactic or preventative agent for the treatment of preeclampsia patients. Pre- eclampsia is developed in pregnant women which cause complications in their pregnancy due to high blood pressure and damage to other body organs. The incidence of Pre-eclampsia is 2-8% of pregnancies, but has a higher risk of about 10% in those females suffering from hypertension or autoimmune diseases. Aim: To know how effectively aspirin is used in preventing the pre-eclampsia in pregnant women who have had the previous history of preeclampsia. Methodology: A randomized controlled trial of aspirin and placebo was conducted. The women enrolled in this study have a gestational period of 6 to 32 weeks. All the women were administrated with 80 mg of placebo or aspirin daily. All the continuous and categorial variables were analyzed statistically and the results were presented as mean±S.D. and frequency(%) for these variables, respectively. Results: All the data was gathered from 260 women who were enrolled in this study. It showed that the occurrence of pre-eclampsia was higher in the placebo group as compared to aspirin group (4.1% vs. 1.6%, p=0004). However, in every risk group, the effects of placebo and aspirin were the same for women with hypertension, the incidence was 13.4% in aspirin and 15.7% in placebo and for women with diabetes, the incidence was 6.7% in aspirin and 6.6% in placebo; but for women with previous history of pre-eclampsia, the incidence was 1.6% in aspirin and 4.1% in placebo which was significantly different. Further, the incidence of pre-eclampsia with primary and secondary outcomes in aspirin and placebo were the same. Conclusion: Our research finding reveals that a low dose of aspirin had a considerable therapeutic effect in preventing pre-eclampsia in high-risk pregnant women.